NILAI MUSYAWARAH DALAM PKN SEBAGAI BASIS PEMBENTUKAN MODAL KULTURAL KOLEKTIF: SEBUAH TINJAUAN PUSTAKA TENTANG DEMOKRASI DELIBERATIF DI SEKOLAH - Setiawan, Yogi; Rohmah, Zulfiani Ainur (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2025)
Civics Education plays a vital role in shaping the democratic character of citizens, yet reality shows low political participation among the younger generation and the dominance of authority in democratic practices in schools. This study aims to explore the value of deliberation in Civics Education as a basis for building collective cultural capital to realize deliberative democracy in educational settings. Using a descriptive qualitative method with a library research approach, this study analyzes various literature related to the challenges of school democracy, the internalization of the fourth principle of Pancasila, and its relationship to modern sociological theory. The results indicate that deliberation functions as a strategic bridge between noble traditional values ??and modern citizenship competencies, capable of fostering critical thinking, empathy, and social responsibility in students. Despite facing technical challenges such as the dominance of vocal students and limited learning time, inclusive teacher facilitation has proven effective in transforming classroom dynamics into a more equal space for dialogue. The main conclusion of this study confirms that substantively integrating the value of deliberation into the curriculum is not only effective in addressing the dialogic deficit but also strengthens the foundation of collective cultural capital, which is essential for the sustainability of a healthy and participatory deliberative democracy in Indonesia's national education system. ABSTRAKPendidikan Kewarganegaraan memegang peran vital dalam membentuk karakter demokratis warga negara, namun realitas menunjukkan masih rendahnya partisipasi politik generasi muda dan adanya dominasi otoritas dalam praktik demokrasi di sekolah. Penelitian ini bertujuan mengeksplorasi nilai musyawarah dalam Pendidikan Kewarganegaraan sebagai basis pembentukan modal kultural kolektif guna mewujudkan demokrasi deliberatif di lingkungan pendidikan. Menggunakan metode kualitatif deskriptif dengan pendekatan studi kepustakaan, penelitian ini menganalisis berbagai literatur terkait tantangan demokrasi sekolah, internalisasi sila keempat Pancasila, serta hubungannya dengan teori sosiologi modern. Hasil kajian menunjukkan bahwa musyawarah berfungsi sebagai jembatan strategis antara nilai tradisi luhur dan kompetensi kewarganegaraan modern yang mampu menumbuhkan sikap kritis, empati, serta tanggung jawab sosial siswa. Kendati menghadapi tantangan teknis seperti dominasi siswa vokal dan keterbatasan waktu pembelajaran, fasilitasi guru yang inklusif terbukti mampu mengubah dinamika kelas menjadi ruang dialog yang lebih setara. Simpulan utama penelitian ini menegaskan bahwa pengintegrasian nilai musyawarah secara substantif dalam kurikulum tidak hanya efektif mengatasi defisit dialogis, tetapi juga memperkuat fondasi modal kultural kolektif yang esensial bagi keberlangsungan demokrasi deliberatif yang sehat dan partisipatif dalam sistem pendidikan nasional Indonesia.